INFORMATION SYSTEM STRATEGIC PLANNING USING WARD AND PEPPARD FRAMEWORK AT THE REGIONAL SECRETARIAT OF BENGKAYANG REGENCY, THE ORGANIZATION SECTION - Angelina Agnes; Agustinus Fritz Wijaya (STMIK Widya Cipta Dharma, 2021)
The Bengkayang Regional Secretariat is a regional apparatus that has the task of formulating policies in Regional Government whose main task is to assist Assistant III in the Administration and General Affairs in institutional arrangement, organizational development, management and performance of regional apparatus. However, this research focuses on the organizational part whose task is to produce output in the form of Regent Regulations, Regional Regulations and Decrees and so on. The purpose of this research is to analyze the use of information systems and propose a number of application portfolios that can support planning and realization to improve office performance. As seen from the development, the office is still working on various tasks manually and there is no information system that supports the operational performance of the office. This information system strategic planning uses the Ward and Peppard framework supported by a SWOT analysis (Strength, Weakness, Opportunities, Threats), Value Chain (main activity and support for internal offices), McFarlan Strategic Grid (Mapping applications). Research with this method provides recommendations that have a big influence in optimizing the application of information systems and increasing the effectiveness of performance so that the vision, mission and goals of the organization can be achieved by following the increasingly rapid development of technology. Proposals for information systems that can be implemented within the next 3 years, namely e-formation, SIOTAK, SI MONEV, SI SPPD and SI Staff Reference.